Surgical treatment of painful lesions of the inferior alveolar nerve. Issue 8 (October 2015) - Biglioli, Federico; Allevi, Fabiana; Lozza, Alessandro
Abstract: Nerve-related complications are being reported with increasing frequency following oral and dental surgery, and typically involve the inferior alveolar nerve (IAN). We assess herein the etiology of neuropathic pain related to IAN injuries, and describe the various surgical treatment techniques available. Between 2007 and 2013, 19 patients were referred to the Maxillofacial Surgery Department of San Paolo Hospital (Milan, Italy) with pain in the area supplied by the IAN, which developed following endodontic treatment, oral surgery and maxillofacial surgery. All patients underwent IAN surgery by several different microsurgical procedures. Most of the patients affected by pain before surgery experienced complete or partial amelioration of symptoms. All patients receiving sural nerve grafts were pain-free 12 months after surgery. In five patients the operation was unsuccessful. In 78.94% of cases, a significant increase in nerve function was observed. Pain following IAN surgical damage may be addressed by microsurgery; nerve substitution with a sural nerve interpositional graft appears to represent the most efficacious procedure. Scar releasing, nerve decompression and nerve substitution using vein grafts are less effective. Removal of endodontic material extravasated into the mandibular canal is mandatory and effective in patients experiencing severe pain. Surgery should be performed within 12 months postoperatively, ideally during the first few weeks after symptoms onset.